First associated tooth set of a high-cusped Ptychodus (Chondrichthyes, Elasmobranchii) from the Upper Cretaceous of northeastern Italy, and resurrection of Ptychodus altior Agassiz, 1835. (January 2019) - Amadori, Manuel; Amalfitano, Jacopo; Giusberti, Luca; Fornaciari, Eliana; Luciani, Valeria; Carnevale, Giorgio; Kriwet, Jürgen
Abstract: Dental remains of the elasmobranch Ptychodus from the Upper Cretaceous of northeastern Italy are described herein. This material, consisting of two slabs containing a partially associated tooth set and additional detached teeth with similar morphological features, derives from different lithozones of the Scaglia Rossa Formation, known as the ʻlastameʼ and ʻPietra di Castellavazzoʼ. All of these teeth are characterized by an unusual high and narrow cusp. The tooth set exhibits elements with different morphologies although they are clearly referable to a single taxon. Based on the species-specific characters of the teeth and according to the Principle of Priority of the International Code of Zoological Nomenclature, we propose herein to resurrect the species Ptychodus altior Agassiz, 1835 as a valid taxon that can easily be separated from P. rugosus Dixon, 1850. Moreover, we designate a neotype of Ptychodus altior Agassiz, 1835 since the type series seemingly is lost. Although similarly developed cusps are observed also in the species Ptychodus rugosus Dixon, 1850 and P. whipplei Marcou, 1858, the material described herein is assigned to Ptychodus altior because of the presence of a narrow cusp with smooth lateral cusp faces. The narrow high-cusped morphology characterizing this species probably indicates a different target prey compared to low-crowned congeneric species. Ptychodus altior is solely known from the Turonian-Coniacian of Europe; we review the distribution and paleobiogeography of this species, extending its range to the Angola region. The fossils described herein represent the first record of Ptychodus altior from Italy and significantly contribute to the knowledge of this species and, more generally, of the paleobiodiversity of the genus Ptychodus in the central Tethys area. Highlights: Description of dental remains of high-cusped Ptychodus. Resurrection of Ptychodus altior Agassiz, 1835 and neotype designation. Comparison with most similar species, Ptychodus rugosus and P. whipplei . Discussion of feeding preference and paleobiogeography of Ptychodus altior .